Kebijakan Peningkatan Profesionalisme Guru dalam Menghadapi Tuntutan Pembelajaran Abad 21 Studi di SD Gmim 3 Woloan - Merentek, Risal M.; Mardiana. P, Rina; Wahab, Syalomita (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the implementation of policies for enhancing teacher professionalism in responding to the demands of 21st-century learning at SD GMIM 3 Woloan. A case study approach was employed, with data collected through classroom observations, interviews with teachers, and school documentation related to training programs and learning modules. The results indicate that some teachers have implemented the policies through Continuous Professional Development training, the use of educational media and technology, the application of the Merdeka Curriculum, and routine collaboration among teachers. The implementation of these policies positively impacts the quality of learning, enhancing student interaction, creativity, motivation, and participation in learning activities. However, several obstacles were also identified, such as limited facilities and infrastructure, variations in teacher competence, and insufficient intensive mentoring, which affect the effectiveness of policy implementation. The study emphasizes the importance of continuous support from schools and educational stakeholders to ensure equitable application of teacher professionalism and maximize its impact on student learning